Molecular biology and pathology of paediatric cancer - Cullinane, Catherine J. (Oxford medical publications., 2003)
This is an important and rapidly changing area and the molecular study of paediatric tumours have contributed enormously to our understanding of the pathogenesis of paediatric oncology. The book provides a comprehensive review of molecular pathology and cytogenetic techniques, looking at the recent developments and their impact on our understanding of aetiology, clinical behaviour, diagnosis and management of paediatric cancer.